The Role of Omega 3 Fatty Acids on Muscle Mass: A Literature Review - Wardhana, Putu Adi Kusuma (Newinera Publisher, 2024)
Omega 3 fatty acids are known to have many benefits for human health, such as regulating lipid metabolism, treating hyperlipidemia, having anti-inflammatory function, increasing brain function and maintaining the body's immune system. Nowadays, among individuals who like to exercise, especially in the field of sports nutrition, omega 3 fatty acids are starting to become popular in their function of maintaining and increasing muscle mass because of their benefits in increasing muscle protein synthesis, reducing muscle damage (exercise-induced muscle damage) after physical exercise or during recovery after exercise so that it can maintain and increase muscle mass. This literature review deepens the benefits of omega 3 fatty acids which can potentially maintain or increase muscle mass. This literature review will discuss the mechanism by which omega 3 fatty acids influence muscle mass through cellular signaling pathways related to muscle protein synthesis which has an impact on a person's muscle mass. This literature review also discusses research results in healthy individuals, the elderly and individuals with chronic ilness. Although several studies show the benefits of omega 3 fatty acids regarding their potential to maintain and increase muscle mass. However, several research results show an insignificant effect of omega 3 fatty acids on muscle mass, causing the benefits of omega 3 fatty acids on muscle mass to continue to be a topic that will continue to be researched, some of the causes may be due to the duration of administration, different doses of administration, different type of omega 3 fatty acids given.